The properties of particleboard composites made from three sorghum (Sorghum bicolor) accessions using maleic acid adhesive - Sutiawan, Jajang (2023)
It is very important to develop green composite materials owing to increasing global environmental issues. One of the alternative raw materials for the production of green composites is biomass. Bagasse sorghum is a promising alternative raw material for the manufacturing of particleboard composites. The influence of sorghum accessions on the performance of particleboard composites was analyzed in this study. In addition, the particleboard quality was made using maleic acid (MA) adhesive and compared with citric acid (CA) and phenol-formaldehyde (PF) adhesives. Three accessions of sorghum, 4183A, super 1, and Pahat, were used as raw materials in particleboard manufacturing. The 20 wt% MA adhesive was applied in particleboard manufacturing. The board dimensions and density targets were 30 × 30 × 0.9 cm3 and 0.8 g/cm3, respectively. The particle mat was pressed 200 °C for 10 min with a maximum of 6.5 MPa. For reference, the JIS A 5908-2003 was used to evaluate physical and mechanical properties, SNI 7207-2014 was used for the resistance against termites, and JIS K 1571-2004 for evaluated the particleboard against decay. The results showed that the sorghum accession in this research did not affect the quality of the particleboard. The thickness swelling (TS), internal bond (IB), modulus of elasticity (MOE), and modulus of rupture (MOR) of particleboard satisfied JIS A 5908-2003 type 8. The particleboard using MA was comparable with those bonded with CA and had better durability against termites and decay than PF adhesives. The ester linkages were formed due to the reaction between MA (carboxyl groups) and the sorghum bagasse (hydroxyl groups) after being analyzed using Fourier transform infrared (FTIR). Therefore, particleboard in this study has good quality.